The human milk endocannabinoidome and neonatal growth in gestational diabetes - Fradet, Alice; Castonguay-Paradis, Sophie; Dugas, Camille; Perron, Julie; St-Arnaud, Gabrielle; Marc, Isabelle; Doyen, Alain; Flamand, Nicolas; Dahhani, Fadil; Di Marzo, Vincenzo; Veilleux, Alain; Robitaille, Julie (Frontiers in Endocrinology, 2024)
Objective Endocannabinoids and their N-acyl-ethanolamines (NAEs) and 2monoacyl-glycerols (2-MAGs) congeners are involved in the central and peripheral regulation of energy homeostasis, they are present in human milk and are associated with obesity. Infants exposed in utero to gestational diabetes mellitus (GDM) are more likely to develop obesity. The objective of this cross-sectional study is to compare the profile of eCBome mediators in milk of women with gestational diabetes (GDM+) and without (GDM-) and to assess the association with offspring growth. The hypothesis is that the eCBome of GDM+ human milk is altered and associated with a difference in infant growth. Methods Circulating eCBome mediators were measured by LC-MS/MS in human milk obtained at 2 months postpartum from GDM+ (n=24) and GDM- (n=29) women. Infant weight and height at 2 months were obtained from the child health record. Z-scores were calculated. Results Circulating Npalmitoylethanolamine (PEA) was higher in human milk of GDM+ women than in GDM- women (4.9 ± 3.2 vs. 3.3 ± 1.7, p=0.04). Higher levels were also found for several 2monoacyl-glycerols (2-MAGs) (p<0.05). The levels of NAEs (β=-4.6, p=0.04) and especially non-omega-3 NAEs (B=-5.6, p=0.004) in human milk were negatively correlated with weight-for-age z-score of GDM+ offspring. Conclusion The profile of eCBome mediators in human milk at 2 months postpartum was different in GDM+ compared to GDM- women and was associated with GDM+ offspring growth at 2 months. Clinical trial registration ClinicalTrials.gov, identifier (NCT04263675 and NCT02872402).